The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/je200434a
|View full text |Cite
|
Sign up to set email alerts
|

Densities and Viscosities of 1-Ethyl-3-methylimidazolium n-Alkyl Sulfates

Abstract: Density and viscosity data for four 1-ethyl-3-methylimidazolium-based ionic liquids combined with alkyl sulfate, [C n SO 4 ] À with n = 1, 4, 6, and 8, and hydrogen sulfate, [HSO 4 ] À , anions were measured at atmospheric pressure in the temperature range 283 < T/K < 363. Isobaric thermal expansion coefficients were calculated from the density results. This work studies the effect of increasing the alkyl chain length of the sulfate-based anion on the density, viscosity, and related properties of this family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 31 publications
8
64
0
Order By: Relevance
“…It can be seen that the differences in the molecular volumes in adjacent ILs are 2.97 nm 3 and this value can be mostly attributed to the inclusion of (-CH 2 ) group by assuming that V=V cation +V anion . In this way, V(-CH 2 )= 2.97 nm 3 which is in good agreement with the value of V(-CH 2 )= 2.80 nm 3 given by Costa et al [64]. Gardas…”
Section: Modelling and Predictionsupporting
confidence: 91%
“…It can be seen that the differences in the molecular volumes in adjacent ILs are 2.97 nm 3 and this value can be mostly attributed to the inclusion of (-CH 2 ) group by assuming that V=V cation +V anion . In this way, V(-CH 2 )= 2.97 nm 3 which is in good agreement with the value of V(-CH 2 )= 2.80 nm 3 given by Costa et al [64]. Gardas…”
Section: Modelling and Predictionsupporting
confidence: 91%
“…The lowest ionic conductivity of 1.51 x 10 -4 S.cm -1 at 25 ºC reports to the chitosan[C 2 mim][C 4 SO 3 ] sample. This sequence was the one expected since the increase of the anion alkyl chain length is associated with an increase of the IL viscosity (18)(19). The increase in viscosity led to a decrease in mobility, which typically tends to be accompanied by a decrease in conductivity.…”
Section: Electrochemical Propertiessupporting
confidence: 63%
“…Figure 1( see also Figure S1) showst hat at any given temperaturet he viscosity of [OH-Emim][FAP] is highert han that of ChemPhysChem 2017, 18,198 -207 www.chemphyschem.org [Emim][FAP],a nd the change in viscosity of these ILs with temperaturec an be well described by Vogel-Tammann-Fulcher relationship. [60] However,t he activation energies of viscousf low of neat [OH-Emim][FAP] and [Emim][FAP] were calculated by plottingl n h versus 1/T to an Arrhenius-type relation [61] ( [18] reported that hydroxyl groups can play as ignificant role in the organization of anionsa round [OH-Emim] + .W hile the acidic hydrogen atom (C2H) of the imidazolium ring in conventional IL is the most probables ite for hydrogen-bonding interactions with anions, [25] the hydroxyl group in [OH-Emim][FAP] providesa na dditional hydrogen-bonding site for cation-anion interionic interactions. Gholamie tal.…”
Section: Thermophysicalp Roperties Of Ilsmentioning
confidence: 99%